2017
DOI: 10.1038/srep45843
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Human Colon Cells from Shiga Toxin by Plant-based Recombinant Secretory IgA

Abstract: Shiga toxin is a major virulence factor of food-poisoning caused by Escherichia coli such as O157:H7. Secretory immunoglobulin (Ig) A (SIgA) is supposed to prevent infection of the mucosal surface and is a candidate agent for oral immunotherapy. We previously established a recombinant monoclonal antibody (mAb) consisting of variable regions from a mouse IgG mAb specific for the binding subunit of Shiga toxin 1 (Stx1) and the Fc region of mouse IgA. Here we produced a secretory form of the recombinant IgA (S-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Exposure of Caco-2 cells to butyrate, a known transcriptional regulator of differentiation genes in many cell types, has been reported to promote the expression of the Stx receptors Gb3Cer and Gb4Cer and toxin sensitivity [ 72 ]. Interestingly, a plant-based recombinant secretory IgA antibody with binding specificity towards the Stx B-subunit, which has been developed as an edible therapeutic antibody for oral immunotherapy, was shown to neutralize the cytotoxicity of Stx1(a) towards butyrate-treated Caco-2 cells [ 96 ]. The internalization of the B-subunit of Stx1 could be significantly lowered by lipid raft disruption by cholesterol depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of Caco-2 cells to butyrate, a known transcriptional regulator of differentiation genes in many cell types, has been reported to promote the expression of the Stx receptors Gb3Cer and Gb4Cer and toxin sensitivity [ 72 ]. Interestingly, a plant-based recombinant secretory IgA antibody with binding specificity towards the Stx B-subunit, which has been developed as an edible therapeutic antibody for oral immunotherapy, was shown to neutralize the cytotoxicity of Stx1(a) towards butyrate-treated Caco-2 cells [ 96 ]. The internalization of the B-subunit of Stx1 could be significantly lowered by lipid raft disruption by cholesterol depletion.…”
Section: Discussionmentioning
confidence: 99%
“…(), and the J‐chain is covalently linked into aggregates that might limit the amount of free J‐chains available to form sSIgA. A bibliographic research showed us how the described effects have been experienced previously by other authors, such as the proteolysis of IgA (Nakanishi et al ., ; Paul et al ., ; Wieland et al ., ), the simultaneous presence of different glycoforms (Juarez et al ., ; Wieland et al ., ) and the proteolysis of the SC (Ma et al ., ; Nakanishi et al ., ), the latter not observed here. These results emphasize the need to thoroughly study molecule stability and protein interactions when working with hetero‐multimeric proteins.…”
Section: Discussionmentioning
confidence: 99%
“…High SIgA levels were obtained, but three sequential crossings were needed to generate the stably transformed line containing the four different loci in homozygous condition. Using a single T‐DNA system in which all the four components required for SIgA production are clustered, significantly reduces the time to develop SIgA‐producing stable transformants as shown for Lemna (duckweed; Ariaans et al ., ) and Arabidopsis thaliana (Arabidopsis; Nakanishi et al ., ). However, the cloning process of this single T‐DNA can be challenging because of the large size of the construct.…”
Section: Introductionmentioning
confidence: 97%
“…Another interesting concept for this strategy is the production of recombinant antibodies or even secretory antibodies specific for Stx by transgenic plants (e.g., thale grass-Arabidopsis thaliana) (Nakanishi et al, 2013(Nakanishi et al, , 2017, a concept that may be transferred to other plants, providing the possibility of an edible therapy.…”
Section: Stx-targeted Antibodiesmentioning
confidence: 99%